Mineralogical Attributes to the Distribution of Trace and Rare Earth Elements in Alteration Zones and Copper-Gold Veins in the Lepanto Copper-Gold Deposit, Luzon, Philippines - Claveria, Rene Juna R (Archīum Ateneo, 2024)
In high sulfidation systems, acidic hydrothermal fluids can produce wide alteration zones with specific mineral assemblages/associations as well as identifiable and elemental distribution patterns. The Lepanto Cu-Au deposit exhibits a consistent zonation pattern of silicic alteration near the Cu-Au veins evolving outwards to advanced argillic and argillic alteration with chloritic alteration farthest from the vein. Recent exploration of high sulfidation Cu-Au veins indicated the usefulness of mineralogical assemblages/associations and the complementing information provided by the elemental distribution patterns in the identification and characterization of the different alteration zones. In this study, I characterize the mineral assemblages/associations and interpret their occurrences in the different alteration zones of the Lepanto Cu-Au deposit. An assemblage that is composed predominantly of chlorite-epidote/clinozoisite-calcite-quartz-pyrite represents the propylitic/chloritic alteration zone. The argillic alteration has a mineral association of smectite-sericite-chlorite-epidote-kaolinite-quartz-pyrite. The advanced argillic alteration zone has alunite-kaolinite-pyrophyllite-diaspore-sericite-quartz-pyrite as mineral association. In the silicic alteration zone, the mineral association is composed of quartz-alunite-diaspore-anhydrite-pyrite. Also presented are the distributions of trace and rare earth elements. In the distribution of trace and REEs across alteration zones, there is an observed increase of Te, Au, Mo, Cu, Sn, and Bi values from the chloritic to silicic alteration zones. A corresponding decrease of REE, LILE (Ba, Pb, Rb, K), HFSE (Ti, Nb, U, Th), Al, Na, Ca, Zn, Mn, Co and Cd values are observed. This study also characterizes the ore mineral assemblages/associations of the Cu-Au veins as well as the distribution patterns of trace and rare earth elements. The Northwest-NOA, hanging wall branch veins (HWBV), main ore body (MOB), foot wall branch veins (FWBV), and Easterlies are generally made up of enargite-luzonite-pyrite-chalcopyrite-tennantite-tetrahedrite-tellurides-covellite. The associated gangue minerals are anhydrite-gypsum-alunite-barite-quartz. In the distribution of elements across the different Cu-Au veins, there is an observed decrease of Cu, As, and Sb values from the Easterlies towards the Northwest-NOA Cu-Au veins. The observed variations in the alteration and ore mineral assemblages/associations have strongly influenced the distribution of elemental values in both alteration zones and Cu-Au veins. The identification of mineralogical assemblages/associations and elemental distribution patterns may provide possible guides and reference tools in the exploration of Lepanto type Cu-Au deposits.